Analyzing technology transfer offices’ influence for entrepreneurial universities in Portugal - Mascarenhas, C.; Marques, C.; Galvão, A.; Carlucci, D.; Falcão, P. F.; Ferreira, F. (Management Decision, 2019)
Purpose: The purpose of this paper is to examine how important technology transfer offices (TTOs) – which in Portuguese are called “industrial property support offices” or GAPIs – are in terms of fostering patent applications and technology transfer in countries characterized by low performance records in these activities. Design/methodology/approach: Among the existing 23 Portuguese GAPIs, only eight agreed to provide answers to a semi-structured questionnaire survey. Content analysis was performed on the data collected using NVivo software. Findings: The results show that GAPIs play an important role in the innovation life-cycle, speeding up the transfer of knowledge and technology to society. The regulation of intellectual property (IP) ownership and royalty sharing with inventors was identified as a major result, strengthening entrepreneurial universities’ role. In addition, after the GAPIs were created, networks were formed that facilitate the sharing of knowledge and experience and promote the development of further collaborative partnerships. Practical implications: This study’s results offer new insights into how GAPIs contribute to socio-economic growth by fostering more entrepreneurial universities and increasing the transfer of technology to society. In addition, these offices promote the creation of networks between GAPIs, enabling them to leverage universities’ potential for participation in socio-economic development. Originality/value: No previous research has focused on GAPIs/TTOs’ point of view regarding policies that enhance IP and technology/knowledge transfer.